Nobody in charge essays on the future of leadership - Cleveland, Harlan (San Francisco Jossey-Bass, 2002)
One of the most renowned thinkers and insightful writers on leadership of our time, Harlan Cleveland has seen numerous trends come and go and weathered many drastic changes in leadership and management-from the rise of the "company man" to the advent of the leaderless, self-managed organization. In this collection of essays-the newest addition to the Warren Bennis Signature Series--he draws on his vast experience to apply his thoughts to leadership. In each essay, Cleveland focuses on an intriguing insight about leadership-illustrated by stories from his own experience --offering thoughtful perspective on what 21st century leaders will face in the new knowledge environment.
Includes index.
Keywords: Leadership